Age and Diabetes Mellitus Associated with Hematological Disorders and Peripheral Neuropathy in MDR-TB Patients Treated with the BPaL/M Regimen - Tako, Frida Welhelmina; Sinaga, Bintang Yinke Magdalena; Harahap, Juliandi; Daulay, Rini Savitri; Siregar, Jelita; Samodra, Yoseph Leonardo (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Tuberculosis (TB) is a disease with a significant treatment burden. Current multidrug-resistant (MDR)-TB therapy uses the bedaquiline, pretomanid, linezolid, and moxifloxacin (BPaL/M) combination. This combination is effective with a short treatment duration. Linezolid is one of the components of the BPaL/M regimen. However, despite its effectiveness, it has side effects that impact treatment management and success. This study aimed to find the association between characteristics and comorbidities with the incidence of linezolid side effects in patients with MDR-TB treated with the BPaL/M regimen. Methods: This was a retrospective analytic study of MDR-TB patients receiving BPaL/M combination. Data were collected from medical records and analyzed using Fisher's exact test to analyze the association between patient characteristics and comorbidities with the incidence of linezolid side effects, namely hematological disorders, peripheral neuropathy, and visual disturbances. Results: There was no significant association between overall patient characteristics and the incidence of linezolid adverse events. However, the results of bivariate analysis showed a significant association in age >50 years old with the incidence of hematological disorders, as well as in patients who have diabetes mellitus (DM) with the incidence of peripheral neuropathy as a side effect of linezolid. Conclusion: Monitoring of MDR-TB patients aged >50 years old and those with DM to minimize the incidence of side effects during treatment is essential. This effort is expected to support the success of the national TB control and treatment program.